Introduction to physics - Cutnell, John D.; Johnson, Kenneth W. (John Wiley & Sons, 2013)
Cutnell and Johnson has been the #1 text in the algebra-based physics market for almost 20 years. PHYSICS 9e continues that tradition by providing superior support students need to facilitate a deeper level of conceptual understanding, improve their reasoning skills and see the relevance of physics to their lives and future careers.